2003
DOI: 10.3354/ame033279
|View full text |Cite
|
Sign up to set email alerts
|

Fate of organic carbon released from decomposing copepod fecal pellets in relation to bacterial production and ectoenzymatic activity

Abstract: Fecal pellets were produced by Acartia tonsa fed 14 C-labeled diatom, cryptophyte, and dinoflagellate diets, and were incubated in 1.2 µm-filtered Long Island Sound seawater. Based on the 14 C label, the decrease in fpOC (fecal pellet organic carbon), the release and fate of dissolved organic carbon (DOC) and particulate organic carbon (POC), as well as bacterial production and enzymatic activity, were followed over a 96 h period. fpOC decreased by 9, 14, and 19% d -1 in diatom, cryptophyte, and dinoflagella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 45 publications
(56 reference statements)
1
43
1
Order By: Relevance
“…The amount of DOC that leaches from copepod faecal pellets is dependent on their food source; amounts being higher when feeding on dinoflagellates compared to diatoms (Thor et al 2003), and when feeding on other heterotrophs compared to phytoplankton (Urban-Rich 1999). Diffusion of DOC from faecal pellets occurs on very short timescales of minutes to hours, in contrast to excretion of DOC from heterotrophs, which occurs over a relatively long timescale of hours to days (Jumars et al 1989;Urban-Rich 1999).…”
Section: Flocculation (F Fl )mentioning
confidence: 99%
“…The amount of DOC that leaches from copepod faecal pellets is dependent on their food source; amounts being higher when feeding on dinoflagellates compared to diatoms (Thor et al 2003), and when feeding on other heterotrophs compared to phytoplankton (Urban-Rich 1999). Diffusion of DOC from faecal pellets occurs on very short timescales of minutes to hours, in contrast to excretion of DOC from heterotrophs, which occurs over a relatively long timescale of hours to days (Jumars et al 1989;Urban-Rich 1999).…”
Section: Flocculation (F Fl )mentioning
confidence: 99%
“…Resale or republication not permitted without written consent of the publisher (Povero et al 2003, Thor et al 2003. In turn, microbes increase the nutritional value of the feces by contributing to the labile organic matter fraction (González & Biddanda 1990, Fabiano et al 1994 through remineralization of dissolved organic matter (Urban-Rich 1999, Povero et al 2003) and uptake of dissolved inorganic nutrients from the water column , Povero et al 2003.…”
Section: Strongylocentrotus Droebachiensismentioning
confidence: 99%
“…In a previous study at Splitnose Point, we observed an exponential loss of fecal mass after defecation (Eq. 2; Sauchyn & Scheibling 2009b), which we attributed to the dissolution of organic matter (DOM) and microbial hydrolysis of particulate organic matter (Urban-Rich 1999, Thor et al 2003). The release of DOM may stimulate microbial activity (Povero et al 2003, Thor et al 2003 and provide nutrients for kelp production (Bert- ) of several species of suspension feeding bivalves, gastropod molluscs, planktivorous reef fish, and blackfly larvae in comparison to the sea urchin Strongylocentrotus droebachiensis ness 1984, Kautsky & Evans 1987).…”
Section: Feces Quality and Degradationmentioning
confidence: 99%
“…However, the similarity of the clearance estimates when either copepod concentration or incubation time were varied (Type 1 and 2 experiments, respectively) suggests that this is a minor source of error, and that microbial degradation played a minor role in visibly removing the fecal pellets. Fecal pellets leak DOC rapidly after egestion, which is utilized primarily by non-attached bacteria (Jumars 1989, Urban-Rich 1999, Thor et al 2003. Leakage of DOM, however, does not change the appearance of the pellets beyond recognition and they may still be counted as intact pellets or fragments.…”
Section: Estimation Of Clearance On Own Fecal Pelletsmentioning
confidence: 99%
“…Fecal pellets produced during the diatom dominated spring bloom are larger, sink faster, are more persistent, and are cleared and degraded at lower rates by copepods due to handling difficulty than pellets produced during a flagellate dominated post-bloom situation (Hansen et al 1996, Feinberg & Dam 1998, Besiktepe & Dam 2002, Thor et al 2003.…”
Section: Ecological Implicationsmentioning
confidence: 99%